Undecided voters ; Manhattan transfer ; Bayani [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Takes a look at Filipino voters preparing for the 1992 election and the SWS election survey; Manhattan Transfer, America's best vocal group, and the production of the film "Bayani" directed by Raymund Red.
Undecided voters (11 min.) -- Manhattan transfer (17 min.) -- Bayani (22 min.)
VHS
Keywords: Red, Raymund -- Interviews; Manhattan Transfer (Singing group).; Voting research -- Philippines; Elections -- Philippines; Motion pictures -- Production and direction -- Philippines